The political ecology of Chinese large dams in Cambodia: implications, challenges and lessons learnt from the Kamchay Dam - Siciliano, Giuseppina; Urban, Frauke; Tan-Mullins, May; Pichdara, Lonn; Kim, Sour (MDPI, 2016)
Given the opportunities offered by foreign investment in energy infrastructure mostly by Chinese firms, the Government of Cambodia is giving high priority to developing hydropower resources for reducing energy poverty and powering economic growth. Using a "Political ecology of the Asian drivers" framework, this paper assesses China's involvement in the development of large dams' in Cambodia and its impacts on the access of natural resources such as water and energy by dam builders, local communities and the government. This analysis is based on 61 interviews and 10 focus group discussions with affected communities, institutional actors, Chinese dam builders and financiers in relation to the first large Chinese dam built in Cambodia: the Kamchay dam. Based on the results of the analysis this paper makes recommendations on how to improve the planning, implementation and governance of future large dams in Cambodia.